Peran Usaha Mikro Kecil Menengah Dalam Pembangunan Ekonomi Perspektif Islam Di Kabupaten Sumbawa - Nisa, Baiq Hidayatun; Apriyani, Dewi; Hidayati, Siti Nur (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2023)
Humans in carrying out various roles as creatures cannot be separated from various needs in order to maintain survival. These needs are related to three basic needs, namely dharuriyat (primary), hajiyat (secondary), and tahsiniyat (tertiary). This research aims to determine the role of Micro, Small and Medium Enterprises in economic development from an Islamic perspective in Sumbawa Regency. The research method used in this study is the literature study method or documents in the form of journals of previous research results, in accordance with the topic of the journal to be reviewed. Micro, Small and Medium Enterprises (UMKM) in economic development in Sumbawa Regency play a very important role because they can absorb labor which increases every year and can increase local revenue derived from levies and taxes from existing UMKM. So this is closely related to the objectives of the Islamic economy of all economic activities to achieve justice and equity (falah).